Naphthalene and Donor Cell Density Influence Field Conjugation of Naphthalene Catabolism Plasmids - Hohnstock, A. M. (American Society for Microbiology, 2000)
We examined transfer of naphthalene-catabolic genes from donor microorganisms native to a contaminated site to site-derived, rifampin-resistant recipient bacteria unable to grow on naphthalene. Horizontal gene transfer (HGT) was demonstrated in filter matings using groundwater microorganisms as donors. Two distinct but similar plasmid types, closely related to pDTG1, were retrieved. In laboratory-incubated sediment matings, the addition of naphthalene stimulated HGT. However, recipient bacteria deployed in recoverable vessels in the field site (in situ) did not retrieve plasmids from native donors. Only when plasmid-containing donor cells and naphthalene were added to the in situ mating experiments did HGT occur.